RhCMV reactivation in SARS-CoV-2 infected aged rhesus macaques - Roh, Jamin W.; Barry, Peter A.; Hunt, Peter W.; Iyer, Smita S.; Shacklett, Barbara L. (Frontiers in Immunology, 2025)
Human Cytomegalovirus (HCMV) is a ubiquitous virus with a global prevalence of 90%, but infection typically has minimal clinical impact in immunocompetent individuals. Consequently, most people are neither tested nor treated for HCMV. However, HCMV seropositivity is associated with higher hospitalization rates following SARS-CoV-2 infection compared to seronegative individuals, suggesting that viral reactivation may exacerbate severity of clinical symptoms. To investigate this, rhesus macaques naturally infected with rhesus cytomegalovirus (RhCMV) were experimentally inoculated with SARS-CoV-2 and monitored. Following inoculation, RhCMV viral loads in plasma increased from baseline, indicating reactivation. Within tissues, the lungs and ileum expressed immediate early protein-1 (IE1), a marker of active RhCMV infection. Additionally, elevated frequencies of circulating activated CD69+ memory T cells at day 3 suggested a recall response to a previously encountered pathogen. These findings demonstrate RhCMV reactivation and associated immune activation following SARS-CoV-2 infection, highlighting the rhesus macaque/RhCMV model as a valuable tool to elucidate the role of HCMV in SARS-CoV2 disease in immunocompetent hosts.